Jeremy brown: secret agent - Cheshire, Simon (Walker Books London, 2004)
Jeremy Brown may look like a weedy schoolboy, but he's actually an MI7 agent. In these stories Jeremy and his sidekick Patsy Spudd battle evil criminals for a communications satellite, fight mummies in Egypt, and travel to Mars. Suggested level: primary, intermediate